Experience of the Multiprofessional Health Team in coping with COVID-19 in Hospitalization Services (Research, Society and Development, 2021)
Objective: to know the perception of the multidisciplinary team about their practice in coping with COVID-19, in a public teaching hospital. Methods: Qualitative study, based on the precepts of discourse analysis. The production of information took place from October to November 2020, 29 health professionals working in the inpatient services of the medical clinic, surgical clinic and oncology clinic of a public hospital were interviewed. Results: With the knowledge of the perception of the multidisciplinary team, five categories were built: Perceiving themselves inserted in the scenario of coping with COVID-19; Experiencing the limitations imposed by the pandemic in the performance of the multiprofessional health team; The vulnerability experienced by the multiprofessional team in facing the pandemic; Multiprofessional team perceives its significant performance in the scenario of COVID-19; Realizing that lessons were learned in coping with the pandemic by COVID-19. Conclusion: The multiprofessional team found itself inserted in an unusual situation, in which it faced adversities which made the professionals resilient to reinvent themselves in the pandemic scenario.